A matter of preference: Taking sides on the Nord Stream 2 gas pipeline project. Issue 2 (3rd April 2022) - de Jong, Moniek; Van de Graaf, Thijs; Haesebrouck, Tim
ABSTRACT: Over the past few years, the Nord Stream 2 gas pipeline has been one of the most divisive issues in EU politics, with some member states opposing the project, others supporting it, and a third group adopting a neutral stance. Which conditions explain these varying national positions? Our study offers the first systematic attempt to examine preference formation with regard to Nord Stream 2 across the entire EU membership. Drawing on elite surveys, we compile an original dataset to position EU member states in the Nord Stream 2 debate. We then perform a Qualitative Comparative Analysis to uncover the determinants of the differing positions taken by member states. The Nord Stream 2 controversy is employed as a testing ground for new intergovernmentalist theory, which argues that preference formation is not just shaped by material and (geo)political conditions, but also by the preferences of other member states. Our study finds that material benefits and the role of Russia are relevant conditions for position formation on Nord Stream 2. However, in this case, we did not find evidence for the importance of other member states' preferences.